Cambodia silenced the press under six regimes - Mehta, Harish C. (1997)
This is the first book on the history of the Khmer press and its struggle for existence under six regimes since the 1930s. The press survived colonial rule, a major coup, genocide, civil war, and Vietnamese occupation. The press was censored and shut down, Khmer journalists were threatened, attacked, and murdered, and several foreign correspondents were captured and killed while covering the civil war. The French denied newspapers licenses to publish, and an equally docile press existed under Sihanouk's rule. Sihanouk wrote arcane and elegant editorials in his journals to rebut criticism in the foreign press about his style of governance. The Lon Nol regime subjected the press to heavy-handed censorship and the Khmer Rouge, on seizing power, shut it down ahead of the genocide. The Heng Samrin regime's journals were never allowed to stray from the official line. Newsmen were still being attacked and murdered after the royal government came to power in 1993, and journalism remained a dangerous profession.